Peningkatan Kapasitas Bisnis AgroEcofarm pada Kelompok P4S Tani Makmur Jaya - Serdani, Army Dita; Puspitorini, Palupi; Fatmawati, Erlin Widya (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
Gogodeso Village consists of settlements, moorland, people's plantations, rice fields with a village area of 383 Ha. In general, livelihoods are identified into several sectors, namely agriculture (mostly), services/trade, industry and others. One of the farmer empowerment programs is the Tani Makmur Jaya Self-Help Agricultural and Rural Training Center (P4S). In its activities, P4S consistently and routinely develops organic farming, one of which is making organic fertilizer and carrying out healthy cultivation practices.   However, they experienced problems with production, management and human resources and marketing. The implementation methods used are: (1) Planning (2) Administrative preparation and team coordination (3) Socialization of Organic Fertilizer (4) Training in Making Organic Fertilizer (5) Management and marketing training (6) Mentoring (7) Supervising related production activities and post-production (8) Evaluation (9) Program sustainability. Community-based empowerment activities in increasing the capacity of AgroEcofarm-based businesses at P4S Tani Makmur Jaya can run smoothly, including the transfer of organic fertilizer technology, transfer of business management and human resources and transfer of marketing branding. In making fertilizer, production can be increased by 2000 bottles of POC/year and 2000 sacks/year of solid organic fertilizer respectively. Apart from that, there are new brands for P4S fertilizer, namely POC Orchomi and Biokosh for solid organic fertilizer.